THE APPLICATION OF ANALYTIC NETWORK PROCESS ANP METHODS FOR COMPANY PROFILE SELECTING ( A CASE STUDY ) - Sutikno Wahyu Hidayat; Ahmadi Ahmadi; Ike Agustiyani; Indra Agustian (JOURNAL ASRO, 2019)
PT. X is a newspaper publishing company. In publishing newspapers, paper raw materials are needed as the main ingredient. In choosing a supplier of paper suppliers, so far the company still applies conventional methods. Improper supplier selection process will have an impact on the sales of the company because it relates to the production process and also the products to be sold later. Many things must be considered in choosing suppliers. In the decision-making process for selecting suppliers, it must be noted that the factors (criteria) that each other might be interrelated. The Analytic Network Process (ANP) method is a method of decision making with many interrelated criteria. This problem is represented in a system with dependence and feedback. The linkages found in the ANP method are linkages in a set of elements (node comparison) and linkages to different elements (cluster comparison). The use of the ANP method will produce priority value weights on all elements contained in the decision making system. From the research that has been done at PT. X there are 4 consideration criteria consisting of 12 sub-criteria, and 3 alternative choices. Based on the results of data processing, alternative suppliers of CV. A was chosen as the best alternative supplier with the highest weight value of 0.158 then CV. B with 0.145 and CV. C of 0.134. Therefore, alternative suppliers of CV. A is the best alternative supplier for the company.